The investigation of the relaxation processes in antiferroelectric liquid crystals by electro-optic spectroscopy - VIJ, JAGDISH KUMAR; PANARIN, YURI PETROVICH (American Institute of Physics, 1998)
Electrooptic spectroscopy of an antiferroelectric liquid crystal is carried out over a range of frequencies from 1 Hz to 100 kHz. In the antiferroelectric SmCA phase two relaxation processes are found, one at the fundamental frequency of a mode and the second at twice the frequency of a different mode. A comparison of the results of the electro-optic spectroscopy with a theoretical study of the motion of the director of an antiferroelectric helix subject to a weak alternating field enables a determination of the origin of the relaxation processes in antiferroelectric phases.
PUBLISHED
Keywords: Electronic & Electrical Engineering